2016
DOI: 10.4097/kjae.2016.69.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Lipofundin® MCT/LCT 20% increase left ventricular systolic pressure in anex vivorat heart model via increase of intracellular calcium level

Abstract: BackgroundLipid emulsions have been used to treat various drug toxicities and for total parenteral nutrition therapy. Their usefulness has also been confirmed in patients with local anesthetic-induced cardiac toxicity. The purpose of this study was to measure the hemodynamic and composition effects of lipid emulsions and to elucidate the mechanism associated with changes in intracellular calcium levels in myocardiocytes.MethodsWe measured hemodynamic effects using a digital analysis system after Intralipid® an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In other words, considering the results of the current tension study and those of previous reports, lipid emulsion-mediated sequestration of bupivacaine, a local anesthetic with relatively high lipid solubility, appears to partly contribute to inhibition of bupivacaine-induced PKC and CPI-17 dephosphorylation [ 3 7 12 23 24 25 26 ]. In addition, lipid emulsion increases [Ca 2+ ] i [ 28 ]. As the conventional PKC α and β isoforms are calcium-dependent isoenzymes, the increased [Ca 2+ ] i induced by lipid emulsion may contribute to attenuation of bupivacaine-induced vasodilation through enhancement of PKC activation during PDBu-induced contraction [ 28 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, considering the results of the current tension study and those of previous reports, lipid emulsion-mediated sequestration of bupivacaine, a local anesthetic with relatively high lipid solubility, appears to partly contribute to inhibition of bupivacaine-induced PKC and CPI-17 dephosphorylation [ 3 7 12 23 24 25 26 ]. In addition, lipid emulsion increases [Ca 2+ ] i [ 28 ]. As the conventional PKC α and β isoforms are calcium-dependent isoenzymes, the increased [Ca 2+ ] i induced by lipid emulsion may contribute to attenuation of bupivacaine-induced vasodilation through enhancement of PKC activation during PDBu-induced contraction [ 28 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lipid emulsion increases [Ca 2+ ] i [ 28 ]. As the conventional PKC α and β isoforms are calcium-dependent isoenzymes, the increased [Ca 2+ ] i induced by lipid emulsion may contribute to attenuation of bupivacaine-induced vasodilation through enhancement of PKC activation during PDBu-induced contraction [ 28 29 ]. However, as lipid emulsion itself had no effect on PDBu-induced contraction ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Fettiplace et al reported that Intralipid® increased the arterial pressure of rats and enhanced the rate of intraventricular pressure increases or decreases in an isolated rat heart model 54 . Lipid emulsion (Intralipid® and Lipofundin® MCT/LCT) increased the intracellular calcium level in H9c2 rat cardiomyoblasts 55 . Moreover, Intralipid® reversed the decreased left ventricular systolic pressure resulting from levobupivacaine-induced myocardial depression of isolated rat hearts using the Langendorff preparation 56 .…”
Section: Proposed Mechanismsmentioning
confidence: 93%
“…Ca level [31]. Also, there are studies, the findings of which are opposite to those in the literature.…”
Section: Discussionmentioning
confidence: 74%